Il diritto verso “il mondo nuovo”. Le sfide dell’Intelligenza Artificiale (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
ABSTRACT: AI is much more than a complex challenge to the system of law. This technology has the potential to change the world and to ask ourselves on the ethical and anthropological questions concerning the deepest meaning of human experi-ence. The contribution investigates the legal implications of the AI systems’ devel-opment, from the responsibilities related to these new forms of behavior, to the risks linked to the profiling and micro targeting of people, to the application of algo-rithmic models in judicial decisions, up to the most radical question: will it be neces-sary or simply possible foreseeing a legal personhood for the artificial “agents”?
Keywords: Artificial Intelligence; legal personhood; responsibility; privacy; algorith-mic justice